2019
DOI: 10.3390/app9112334
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Defect Localization in a Cross-Ply Fiber Reinforced Composite with Diffuse Ultrasonic Waves

Abstract: Diffuse wave inspection benefits from multiple scattering and is suitable for the nondestructive testing of complex structures with high sensitivity. This paper aims to localize the defect in a cross-ply carbon fiber reinforced polymer composite with the diffuse wave field experimentally based on the Locadiff technique. Firstly, the wave diffusivity and dissipation parameters are determined from the diffuse waveforms. Great dissipation is found for this composite plate due to its strong viscoelasticity, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Most of the papers of this special issue involve fiber reinforced composites [7][8][9][10][11][12]. These include different types of matrices and fibers that are used for different applications going from the transport industry (aircraft, trains, ships, etc.)…”
Section: Nondestructive Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the papers of this special issue involve fiber reinforced composites [7][8][9][10][11][12]. These include different types of matrices and fibers that are used for different applications going from the transport industry (aircraft, trains, ships, etc.)…”
Section: Nondestructive Testingmentioning
confidence: 99%
“…The information contained in diffuse waves are mostly useful in seismology and in civil engineering, but can be also used for health monitoring and the nondestructive evaluation of fiber reinforced composites. Zhu et al [8] applied this method to the inspection of carbon/epoxy and found it promising for early crack detection. A critical aspect for defect localization is to distinguish signals from noise, and this requires more investigation.…”
Section: Nondestructive Testingmentioning
confidence: 99%
“…Ultrasonic techniques are based on the propagation of elastic waves through the object to be examined and monitoring the transmitted signal or the reflected/diffracted signal. The techniques have good versatility but present shortcomings as regards the reconstruction of the shape of a defect [9,17,18]. The eddy current (ECs) method is highly versatile as it allows any application that can be correlated to the variations in the chemical-physical characteristics of any conductor [15,19].…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistics in 2014, the global consumption of polyurethane has exceeded 21.5 million tons, and the foam products have become the focus of polymer material design with the annual consumption exceeding 11.5 million tons [24]. In addition, polyurethane materials used in the project also become a main branch of polyurethane materials with an annual consumption of about 2 million tons.…”
Section: Introductionmentioning
confidence: 99%